Genomic Comparison among Lethal Invasive Strains of Streptococcus pyogenes Serotype M1 - Fernandes, Gabriel R.; Barbosa, Aulus E. A. D.; Almeida, Renan N.; Castro, Fabíola F. dos S.; da Ponte, Marina de C. P.; Faria-Junior, Celio; Müller, Fernanda M. P.; Viana, Antônio A. B.; Grattapaglia, Dario; Franco, Octavio L.; Alencar, Sérgio A.; Dias, Simoni C. (Frontiers in Microbiology, 2017)
Streptococcus pyogenes, also known as group A Streptococcus (GAS), is a human pathogen that causes diverse human diseases including streptococcal toxic shock syndrome (STSS). A GAS outbreak occurred in Brasilia, Brazil, during the second half of the year 2011, causing 26 deaths. Whole genome sequencing was performed using Illumina platform. The sequences were assembled and genes were predicted for comparative analysis with emm type 1 strains: MGAS5005 and M1 GAS. Genomics comparison revealed one of the invasive strains that differ from others isolates and from emm 1 reference genomes. Also, the new invasive strain showed differences in the content of virulence factors compared to other isolated in the same outbreak. The evolution of contemporary GAS strains is strongly associated with horizontal gene transfer. This is the first genomic study of a Streptococcal emm1 outbreak in Brazil, and revealed the rapid bacterial evolution leading to new clones. The emergence of new invasive strains can be a consequence of the injudicious use of antibiotics in Brazil during the past decades.